From Conventional to Innovative Approaches for Pain Treatment 2019
DOI: 10.5772/intechopen.84195
|View full text |Cite
|
Sign up to set email alerts
|

Food-Derived Opioids: Production and the Effects of Opioids on Human Health

Abstract: Traditional opioids have been used for the people who suffer from cancer, burns, surgery, HIV/AIDS, and other serious illness pains for years. However, numerous side effects like dizziness, apnea, physical dependence, tolerance, addiction, nausea, and vomiting push the researchers to look forward to the new opioid options. The opioid peptides which derived from foods provide significant advantages as the safe and natural alternative. The researchers reported that it is also promising a new functional food and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…Это разрушение может усугубляться выработкой антител против бета-казеина. Данные от почти 1300 образцов сыворотки показали, что у всех исследуемых были верифицированы антитела против казеина, с самыми высокими показателями титров антиказеина A1 среди лиц, страдающих инсулинозависимым сахарным диабетом [17].…”
Section: казеин и казморфиныunclassified
“…Это разрушение может усугубляться выработкой антител против бета-казеина. Данные от почти 1300 образцов сыворотки показали, что у всех исследуемых были верифицированы антитела против казеина, с самыми высокими показателями титров антиказеина A1 среди лиц, страдающих инсулинозависимым сахарным диабетом [17].…”
Section: казеин и казморфиныunclassified
“…The amino acid composition and sequence determine the peptides' physiological function. These peptides can be classified as antimicrobial (antifungal, antibacterial) (29,30), anti-inflammatory (31, 32), anticancer (33), antihypertensive (34,35), immunomodulatory (36), mineral-binding (37), opioids (38), and antidiabetic (39)(40)(41), based on the experimentally determined functionality. It has been reported that some peptides are multifunctional; thus, they can exhibit more than one biofunction (5,42).…”
Section: Introductionmentioning
confidence: 99%